Pengaruh Struktur Modal, Profitabilitas dan Kebijakan Dividen Perusahaan Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019) - Tagor Darius Sidauruk; Adolpino Nainggolan; Gina Regina (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
The purpose of the study was to determine the effect of capital structure (DER), profitability (ROE), and dividend policy (DPR) on firm value (PBV). The research population is manufacturing companies listed on the Indonesia Stock Exchange in 2016-2019. The sampling technique was purposive sampling, which was 88 samples. Analysis of research results using multiple linear regression analysis. The results of the study of profitability (ROE) and dividend policy (DPR) variables have a positive effect on firm value, then the capital structure variable (DER) has no effect on firm value.